2019
DOI: 10.1021/acsomega.8b03067
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the Performance of a Visible–NIR Photodetector Using Horizontally Aligned TiS3 Nanoribbons

Abstract: We report the fabrication and characterization of visible and near-infrared-resistive photodetector using horizontally aligned titanium tri sulfide (TiS 3 ) nanoribbons. The fabrication process employed micro-electromechanical system, photolithography and dielectrophoretic (DEP) methods. The interdigitated electrodes (IDE) fingers were fabricated using photolithography and thin-film metallization techniques onto the Si/SiO 2 substrate, and then TiS 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 74 publications
1
25
1
Order By: Relevance
“…[15,16] MS 3 is considered to have great potential in application of optical and electronic devices because of its unique quasi-1D crystal structure and strong optical anisotropy. [11,[17][18][19][20][21][22] Previous studies have shown that the dichroic ratio of TiS 3 is 4:1 [16] and that of ZrS 3 is 2.55:1. [15] The best excitation energy of the dichromatic ratio generated by photocurrent was 1.00-2.0 eV for TiS 3 and 2.0 to 3.0 eV for ZrS 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] MS 3 is considered to have great potential in application of optical and electronic devices because of its unique quasi-1D crystal structure and strong optical anisotropy. [11,[17][18][19][20][21][22] Previous studies have shown that the dichroic ratio of TiS 3 is 4:1 [16] and that of ZrS 3 is 2.55:1. [15] The best excitation energy of the dichromatic ratio generated by photocurrent was 1.00-2.0 eV for TiS 3 and 2.0 to 3.0 eV for ZrS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 15,16 ] MS 3 is considered to have great potential in application of optical and electronic devices because of its unique quasi‐1D crystal structure and strong optical anisotropy. [ 11,17–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…It represents the ability of the detector to capture the weakest signal, which can be mathematically expressed as [71]:…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The ratio of photocurrent to the incident intensity of the laser wavelength λ is defined as photoresponsivity of the photodetector and it can be calculated as [ 71 ]: …”
mentioning
confidence: 99%
See 1 more Smart Citation